2023
DOI: 10.1186/s13019-023-02271-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between transcatheter tricuspid valve repair and surgical tricuspid valve replacement or repair in patients with tricuspid insufficiency

Abstract: Background Tricuspid regurgitation is associated with significant morbidity and mortality, but with limited treatment options. The objective of this study is to compare the demographic characteristics, complications, and outcomes of transcatheter tricuspid valve repair (TTVr) versus surgical tricuspid valve replacement (STVR) or surgical tricuspid valve repair (STVr), using real-world data from the National Inpatient Sample (NIS) database. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…65 It is notable that, compared with patients who are treated with transcatheter tricuspid therapies, patients treated with TV surgery are significantly younger. 66 Long-term survival and durability data remain rather limited, likely because of limited follow-up in this cohort. A team-based approach to the preoperative and perioperative patient selection and management of patients in conjunction with HF physicians is imperative.…”
Section: Surgerymentioning
confidence: 93%
“…65 It is notable that, compared with patients who are treated with transcatheter tricuspid therapies, patients treated with TV surgery are significantly younger. 66 Long-term survival and durability data remain rather limited, likely because of limited follow-up in this cohort. A team-based approach to the preoperative and perioperative patient selection and management of patients in conjunction with HF physicians is imperative.…”
Section: Surgerymentioning
confidence: 93%
“…In this line, Wang et al . [ 61 ] analyzed demographic characteristics, complications, and outcomes of 92, 86, and 84 TR patients who underwent TR surgical repair (STVr) or replacement (STVR), and transcatheter repair (TTVr), respectively, using real-world data from the National Inpatient Sample (NIS) database. The study found that TTVr patients were significantly older than STVr (65.03 years in STVr, 66.3 years in STVR, 71.09 years in TTVr, p 0.05).…”
Section: Ttvi Versus Surgical Approachmentioning
confidence: 99%
“…Patients who received STVr or STVR presented a higher mortality rate (8.7% and 3.5%, respectively) compared to TTVr (1.2%), and were more likely to experience perioperative complications, including third-degree atrioventricular block, respiratory failure, respiratory complications, and acute kidney injury. Moreover, costs of care (USD$ 37,995 356,008.523 STVr vs. USD$ 198,397 188,943.082 TTVr, p 0.05; USD$ 470,948 614,177.568 STVR vs. USD$ 198,397 188,943.082 TTVr, p 0.05) and hospital lengths-of-stay (15.4 15.19 STVr vs. 9.6 10.21 days TTVr, p = 0.267; 24.7 28.81 STVR vs. 9.6 10.21 days TTVr, p 0.05) were higher for STVr or STVR than for TTVr [ 61 ].…”
Section: Ttvi Versus Surgical Approachmentioning
confidence: 99%